Geniposide Alleviates Isoproterenol-Induced Cardiac Fibrosis Partially via SIRT1 Activation in vivo and in vitro - Li, Ning; Zhou, Heng; Ma, Zhen-Guo; Zhu, Jin-Xiu; Liu, Chen; Song, Peng; Kong, Chun-Yan; Wu, Hai-Ming; Deng, Wei; Tang, Qi-Zhu (Frontiers in Pharmacology, 2018)
Objective: Geniposide (GE) is a major component in the fruit of Gardenia jasminoides Ellis. Oxidative stress, endoplasmic reticulum (ER) stress and canonical Smad3 pathway are implicated in the pathogenesis of cardiac fibrosis. We aim to investigate the protective roles of GE in pathological cardiac fibrosis. Methods: Male C57BL/6 mice induced by isoprenaline (ISO) were used to construct a model of cardiac fibrosis. GE and the EX-527 was given for 2 weeks to detect the effects of GE on cardiac fibrosis. Levels of oxidative stress, ER stress and Smad3 were evaluated by Real time (RT)-PCR, Western blots, immunohistochemistry staining, immunofluorescence staining, and assay kits. Results: GE treatment alleviated cardiac dysfunction, fibrosis and hypertrophy in mice response to ISO. Additionally, GE also suppressed the transformation of cardiac fibroblasts to myofibroblasts stimulated by transforming growth factor-β (TGF-β) in vitro. Mechanistically, GE inhibited the oxidative stress, ER stress as well as Smad3 pathway activated by ISO or TGF-β. A selective antagonist of SIRT1, EX-527, partially counteracted the anti-fibrotic effect and weakened the inhibitory effect on the transformation of cardiac fibroblasts to myofibroblasts after the treatment of GE. Acetylated Smad3 (ac-Smad3), oxidative stress as well as ER stress pathway were significantly enhanced after SIRT1 was blocked while phosphorylated Smad3 (P-Smad3) was not affected. Conclusion: GE could combat cardiac fibrosis in vivo and vitro by inhibiting oxidative stress, ER stress and ac-Smad3 in a SIRT1-dependent manner and suppressing P-Samd3 pathway independent of SIRT1 activation. GE is expected to be a promising agent against cardiac fibrosis.